Предмет: Алгебра,
автор: kuzmindl2
Срочно! х(х(х-1))+6=х(х+3)(х-4)
Ответы
Автор ответа:
0
х (х в квадрате-х) +6=х (х в квадрате- 4х +3х-12)
х в кубе - х в квадрате=6= х в кубе - 4х в квадрате+ 3х в квадрате-12х
-х в квадрате+хв квадрате+12х=-6
х=-0,5
х в кубе - х в квадрате=6= х в кубе - 4х в квадрате+ 3х в квадрате-12х
-х в квадрате+хв квадрате+12х=-6
х=-0,5
Похожие вопросы
Предмет: Химия,
автор: podkosov1
Предмет: Математика,
автор: ksenialatkina977
Предмет: Химия,
автор: felleranastasia9484
Предмет: Математика,
автор: Satiya
Предмет: Физика,
автор: marinabolshakova